2012
DOI: 10.5194/acp-12-4525-2012
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic growth and droplet activation of soot particles: uncoated, succinic or sulfuric acid coated

Abstract: Abstract. The hygroscopic growth and droplet activation of uncoated soot particles and such coated with succinic acid and sulfuric acid were investigated during the IN-11 cam-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 58 publications
(66 reference statements)
6
42
0
Order By: Relevance
“…These results are consistent with past studies that failed to find sub-saturated hygroscopic growth or supersaturated CCN activation (s ≤ 1%) for uncoated Mini-CAST soot (Friedman et al 2011;Henning et al 2012). Popovicheva et al (2008) used a gravimetric method to measure sub-saturated water uptake on CAST burner soot at two conditions: flame C/O ratio of 0.29 (4% OC) and 0.4 (27% OC), which are the same conditions examined by Möhler et al (2005).…”
Section: Soot Hygroscopicitysupporting
confidence: 79%
See 1 more Smart Citation
“…These results are consistent with past studies that failed to find sub-saturated hygroscopic growth or supersaturated CCN activation (s ≤ 1%) for uncoated Mini-CAST soot (Friedman et al 2011;Henning et al 2012). Popovicheva et al (2008) used a gravimetric method to measure sub-saturated water uptake on CAST burner soot at two conditions: flame C/O ratio of 0.29 (4% OC) and 0.4 (27% OC), which are the same conditions examined by Möhler et al (2005).…”
Section: Soot Hygroscopicitysupporting
confidence: 79%
“…Operation is safe, stable, and capable of generating high concentrations of soot (Jing 1999). Consequently, a large number of studies have used the Mini-CAST (or a similar, larger CAST) burner to study coated or uncoated soot in terms of optical properties, ice nucleation, and cloud droplet nucleation (Möhler et al 2005;Schnaiter et al 2006;Crawford et al 2011;Henning et al 2012). Typically, a few burner conditions are used to create soot of varying OC:EC ratios, which are well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The cloud forming properties of soot can be altered, and climate forcing can be influenced (albeit indirectly), by coating the soot with soluble material. For example, atmospheric ageing of coated soot enhances the hygroscopicity of the coatings and, hence, aged soot particles can act as efficient cloud condensation nuclei (CCN) or ice nuclei (IN) (Ammann et al, 1998;Henning et al, 2012). Transformation from fresh hydrophobic soot to processed hygroscopic soot can also have adverse health effects as, compared with hydrophobic fresh soot, aged hygroscopic soot has an altered deposition in the lungs (Löndahl et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction also included hygroscopic shrinkage. Hygroscopic GFs up to 1.11 were obtained with succinic acid at 98% RH for particles with 375 and 500 nm dry diameter (Henning et al, 2012). It has to be noted that succinic acid coating on soot particles appears to be a good example for oxygenated organic substances in atmospheric environments strongly influenced by biogenic activities, while the situation with the coatings in urban environments can be different.…”
mentioning
confidence: 99%
“…The tendencies in the hygroscopic and volatile properties, and in the particle number fraction of modes mentioned above are ordinarily observed in urban VH-TDMA studies (e.g., Ferron et al, 2005) since the particle number size distribution of soot from traffic emissions peaks between 50 and 100 nm (Weingartner et al, 1997). It was previously concluded that uncoated fresh soot particles (although of somewhat larger diameters than 145 nm) showed neither hygroscopic growth nor water activation, while their coating with succinic acid, sulphuric acid or polyaromatic hydrocarbons (PAHs) influenced the hygroscopic growth in a complex way (Henning et al, 2012). The diameter change depended on the amount and type of the coatings, on the "humidity history" of particles (coating 5 by solution layer or solid film) and on the carrier gas used in the experiments.…”
mentioning
confidence: 99%